Forever transnational: The ambivalence of return and cross-border activities of the Shan across the Thailand-Myanmar border - Jirattikorn A. (2017)
© 2017 Department of Geography, National University of Singapore and John Wiley & Sons Australia, Ltd Over the past two decades, northern Thailand has experienced a massive influx of Shan ethnic nationals from Myanmar migrating to escape economic hardship and political conflicts at home. Myanmar's recent reforms raise the question of whether these migrants will return. The paper brings together the context of current changes in Myanmar with migrants' prospects of return and the impact of large-scale migration on homeland politics. On the one hand, the paper explores the possibility that Shan migrants could remain forever transnational, for many of them will most likely never return. On the other hand, it considers the perspective of Shan elites in Myanmar on the fact a large portion of young Shan now spend their adult lives living and working in Thailand. While out-migration of young Shan threatens the social fabric of Shan community in Myanmar, Shan ethnonationalists strive across the Myanmar border to regain loyalty among the Shan migrant population in Thailand. By examining the two aspects, this paper attempts to shed light on the impact of transnational migration on both migrants and their home country.